Improving the Performance of Palopo DPRD Secretariat Employees through Work Mutations and Interpersonal Conflicts - Hadriati Hadriati; Muh. Yusuf Q; Andi Nadirah Mahmud (Institute of Computer Science (IOCS), 2022)
This study aims to (1) describe the performance improvement of the Palopo DPRD Secretariat employees (2) analyze the effect of work mutations, and interpersonal conflicts on the performance of the Palopo DPRD Secretariat employees. The method used is a quantitative method which is processed with the SPSS program, using a population and a sample. Analysis of the data used with Multiple Linear Regression Analysis. In this study, the population was all employees of the DPRD Palopo City as many as 32 people who had their address at Jalan A. Baso womb no.1 Palopo City within the study period for 1 week. While the sample to be surveyed is taken according to the Census Law, the entire population is used as the survey sample. The data was collected by means of a questionnaire technique or the distribution of questionnaires. The equation for this regression test is Y = 16,692 + 0,239 X1 +(-0,100) X2 + e, for the t value of employee performance (Y) = 16,692 t value of work mutations (X1) = 0.239 t value of interpersonal conflict (X2) =(- 0.100) then from the equation it can be seen that all independent variables have no significant effect on employee performance. The Adjusted R square value is 0.100. For the calculated F value of 1.548 and a significant value of 0.230 while the value of is 0.05 so that the work mutation and interpersonal conflict variables together or simultaneously have no significant effect on employee performance. Based on the results of the study, to improve employee performance at the Palopo City DPRD Office, several other factors must be considered apart from these two variables. Subsequent research pays attention to the number of samples used so that the intended target is closer.